2016
DOI: 10.1093/neuonc/nov318
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of HER2-amplified brain tumors with targeted NK-92 cells and focused ultrasound improves survival

Abstract: Many tumor proteins could be exploited for targeted therapy with the NK-92 cell line; combined with the mounting safety evidence for transcranial ultrasound, these results may soon be translatable to a highly targeted treatment option for patients with brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 28 publications
1
83
0
Order By: Relevance
“…Interestingly, in our study as well as studies by Park (Park et al 2012) an Alkins (Alkins et al 2016) a response was observed only in some of the animals. Both studies used tumor model based on HER2-positive cells from a breast cancer patient.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, in our study as well as studies by Park (Park et al 2012) an Alkins (Alkins et al 2016) a response was observed only in some of the animals. Both studies used tumor model based on HER2-positive cells from a breast cancer patient.…”
Section: Discussionsupporting
confidence: 63%
“…27 These cells have been studied both preclinically, and now clinically as a stand-alone anticancer therapeutic. 28,29 In addition, these cells do not display CD5 on their surface, which allows for expression of the CD5-VLR-CAR without self-activation and killing of transduced cells. Given the poor transduction efficiency of NK-92 cells (<10%), a construct incorporating a GFP P2A sequence was created (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…So far, the following statements can be made: the ARF pushes microbubbles toward the vascular wall and promotes an impact on vascular cells that induces a loose intercellular gap; and microbubbles inside the vasculature can produce microstreams and shock waves, thus compromising the stability of the vascular wall. After the safe BBB disruption with focused ultrasound (FUS) and microbubbles (Figure 6), NK-92 cells are largely delivered into brain tumor tissues and exert their anticancer effects, causing a higher suppression of tumor growth and longer survival time in a mouse brain tumor model compared to the non-treatment prototype 81. Alkins et al labeled HER2 high-expressing breast tumor cells with superparamagnetic iron oxide (SPIO) and implanted them into nude rats.…”
Section: Immunotherapy Assisted By Ummdmentioning
confidence: 99%